Cardiovascular magnetic resonance imaging in patients with cardiac implantable electronic devices: best practice and real-world experience. Issue 8 (25th May 2019) - Seewöster, Timm; Löbe, Susanne; Hilbert, Sebastian; Bollmann, Andreas; Sommer, Philipp; Lindemann, Frank; Bacevičius, Justinas; Schöne, Katharina; Richter, Sergio; Döring, Michael; Paetsch, Ingo; Hindricks, Gerhard; et al.
Abstract: Aims: Cardiovascular magnetic resonance (CMR) imaging has long been a contraindication for patients with a cardiac implantable electronic device (CIED). Recent studies support the feasibility and safety for non-thoracic magnetic resonance imaging, but data for CMR are sparse. The aim of the current study was to determine the safety in patients with magnetic resonance (MR)-conditional or non-MR-conditional CIED and to develop a best practice approach. Methods and results: All patients with a CIED undergoing CMR imaging (1.5 T) between April 2014 and April 2017 were included in the study. Devices were programmed according to the standardized protocol directly before and after the CMR examination. Follow-up interrogation was performed 6 months after CMR examination. Results were compared with a large, reference cohort of CIED patients not undergoing any MR examination. A total of 200 consecutive patients with a CIED (non-MR-conditional, n  = 103) were included in the study. Directly after CMR imaging, one device failure (0.5%, battery status = end of service) was noted necessitating premature generator replacement. In three patients (2%) of pacemaker/implantable cardioverter-defibrillator (ICD) carriers a sustained ventricular tachycardia (VT) occurred during CMR imaging. Ten ICD showed a decrease in battery capacity immediately after CMR. Overall, the reference cohort showed comparable changes of CIED function during follow-up. Conclusion: With adherence to a standardized protocol and established exclusion criteria CMR imaging could safely be performed in patients with a CIED. The potential risks of device malfunction necessitate the presence of a device trained individual during the entire CMR examination. If there is a history of VT storm the attendance of an experienced cardiologist, should be mandatory.